Pengaruh Gaya Kepemimpinan, Budaya Organisasi, Fasilitas Kerja Terhadap Kinerja Pegawai (Study Pada Ministerio Comêrcio E Industria Timor-Leste) - Freitas, Nizia Felismina Araujo; Slamet, Afi Rachmat; Ramadhan, Tri Sugiarti (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research was conducted to determine the influence of leadership style, organizational culture, and work facilities on the performance of Ministerio e comercio noindustria (Timor-Leste) employees. The population in this study was 257 Ministerio Comȇrcio e Industria.de (Timor-Leste) employees. The sample collection technique was based on certain criteria using a questionnaire distributed to 72 respondents and using the SPSS analysis tool. The research results show that the variables of leadership style, organizational culture, and work facilities have a simultaneous and partial effect on employee performance. Keywords: Leadership style, organizational culture, work facilities, employee performance